2006
DOI: 10.21236/ada459422
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Research on Infrared Detection

Abstract: Public Reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comment regarding this burden estimates or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for information Operations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Zhang et al [39] investigated martensitic FeeNi alloys aged in the 300e450 C temperature range and measured a-Fe and g-(Fe, Ni) FM phase compositions in this range. They did not find experimental evidence of the monotectoid equilibrium at temperature lower than 400 C. Combining the results of previous investigations [28,30,31,39] with new measurements on meteoric samples Yang, Williams and Goldstein [12] concluded that the monotectoid equilibrium should occur at about 400 C with phase compositions of about 6 [28], 40 and 46 at% Ni [39] for a-Fe, g-(Fe,Ni) PM and g-(Fe, Ni) FM , respectively.…”
Section: High Temperature Equilibria (T > 1000 C)supporting
confidence: 68%
See 4 more Smart Citations
“…Zhang et al [39] investigated martensitic FeeNi alloys aged in the 300e450 C temperature range and measured a-Fe and g-(Fe, Ni) FM phase compositions in this range. They did not find experimental evidence of the monotectoid equilibrium at temperature lower than 400 C. Combining the results of previous investigations [28,30,31,39] with new measurements on meteoric samples Yang, Williams and Goldstein [12] concluded that the monotectoid equilibrium should occur at about 400 C with phase compositions of about 6 [28], 40 and 46 at% Ni [39] for a-Fe, g-(Fe,Ni) PM and g-(Fe, Ni) FM , respectively.…”
Section: High Temperature Equilibria (T > 1000 C)supporting
confidence: 68%
“…The a-Fe þ g-(Fe,Ni) two-phase field ends at a monotectoid equilibrium g-(Fe,Ni) PM $ a-Fe þ g-(Fe,Ni) FM (where PM refers to a paramagnetic state and FM a ferromagnetic state) first proposed by Nishizawa [29] and subsequently calculated by Chuang et al [30,31], but not observed experimentally.…”
Section: High Temperature Equilibria (T > 1000 C)mentioning
confidence: 98%
See 3 more Smart Citations